The Effect of Liquid Smoke on Chlorophyl Levels In Green Plants (Brassica juncea L) - Sary, Novita; Sri Hartanti, Dyah Ayu; Puspaningrum, Yessita (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The green mustard plant (Brassica juncea L) is a plant that can adapt well to places with hot or cold air. Liquid smoke is known to contain various bioactive compounds that can affect chlorophyll levels in mustard plants. This research uses quantitative methods to determine the effect of liquid smoke on chlorophyll levels in mustard green plants. This research was carried out on mustard green plants that were given liquid smoke from certain fuels in a laboratory environment. The variable measured was the chlorophyll content in plant leaves, which is considered the main indicator of plant photosynthetic health. This research used a randomized block design with two treatments, namely a control group without administration of liquid smoke and a treatment group with liquid smoke for a certain period of time. Chlorophyll levels were measured using the Uv-Vis Spectrophotometry method. The results of this study showed that control mustard greens had a total chlorophyll content of 10.28 mg/L and mustard greens with liquid smoke had a total chlorophyll content of 7.47 mg/L. Control mustard greens had a higher chlorophyll content than mustard greens treated with liquid smoke.